Ethical And Philosophical Basis Of Compliance With Traffic Rules - Sidikov Sardor Nematullayevich (Peerian Journals Publishing, 2025)
This article describes the philosophical and legal basis of traffic rules. Moral education is an important tool that has an active influence on the life of society and people. In the analysis of traffic safety culture, it is important to monitor the activities of road traffic participants and provide explanations on their correct decision-making
Keywords: Traffic; safety; analysis